2020
DOI: 10.1055/a-1067-4563
|View full text |Cite
|
Sign up to set email alerts
|

Self-expanding metal stents versus TIPS in treatment of refractory bleeding esophageal varices: a systematic review and meta-analysis

Abstract: Background and study aims Refractory and recurrent esophageal variceal (EV) bleeding can be life threatening. Self-expanding metal stents (SEMS) have been used as a “bridge” therapy. However, their role in the treatment protocol is not established due to paucity in data. Methods We searched multiple databases from inception through May 2019 to identify studies that reported on SEMS and TIPS in refractory EV hemorrhage. Our primary goals were to analyze and compare the pooled all-cause mortality, imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Esophageal stent placement for acute variceal bleeding has mainly been investigated in small retrospective studies using a dedicated stent design (SX-ELLA stent DANIS) for the treatment of refractory bleeding (Table 6s). Stent duration is reported to range from 1-30 days [126]. Pooled data analysis shows that SEMS placement leads to control of bleeding in > 80 % of patients, without severe stent-related adverse events [126,127].…”
Section: Acute Variceal Bleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal stent placement for acute variceal bleeding has mainly been investigated in small retrospective studies using a dedicated stent design (SX-ELLA stent DANIS) for the treatment of refractory bleeding (Table 6s). Stent duration is reported to range from 1-30 days [126]. Pooled data analysis shows that SEMS placement leads to control of bleeding in > 80 % of patients, without severe stent-related adverse events [126,127].…”
Section: Acute Variceal Bleedingmentioning
confidence: 99%
“…Stent duration is reported to range from 1-30 days [126]. Pooled data analysis shows that SEMS placement leads to control of bleeding in > 80 % of patients, without severe stent-related adverse events [126,127]. In 21 % of patients, bleeding reoccurs within 6 weeks after SEMS placement [128].…”
Section: Acute Variceal Bleedingmentioning
confidence: 99%
“…A randomized control study showed that SEMSs have greater efficacy with less-severe adverse events than balloon tamponade in the control of esophageal variceal hemorrhaging ( 11 ). Although the use of SEMSs for refractory variceal bleeding has shown good immediate bleeding control with an acceptable technical success rate, the mortality and rebleeding rates were reported to be higher than those of TIPS in a meta-analysis ( 12 ). Thus, according to the European Society of Gastrointestinal Endoscopy (ESGE) Guideline, the use of SEMSs is considered as a temporal bridge therapy to TIPS ( 13 ), and we did not consider the use of SEMSs to be a positive option.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of refractory acute variceal bleeding, several systematic reviews and meta-analyses [ 89 , 90 , 91 ] support use of SEMS in successful control of severe or refractory acute variceal bleeding, without significant device-related AEs (Fig. 5 ).…”
Section: Esophageal Stentingmentioning
confidence: 99%